2013
DOI: 10.1016/j.gene.2012.10.038
|View full text |Cite
|
Sign up to set email alerts
|

The impact of GGH -401C>T polymorphism on cisplatin-based chemoradiotherapy response and survival in cervical cancer

Abstract: Aims: Cervical cancer is the third most frequent cancer in women worldwide, mostly treated with cisplatin-based chemoradiotherapy. Since it is known that folate metabolism might interfere with cisplatin effectiveness, we intended to study the influence of the Gamma Glutamyl Hydrolase -401C > T polymorphism in treatment response in cervical cancer. Methods: We retrospectively reviewed the clinical data of 167 patients with bulky cervical cancer submitted to cisplatin-based chemoradiotherapy. The genotypes of GG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
3
2
0
Order By: Relevance
“…Previous studies have reported higher GGH expression levels in urothelial, invasive breast, ERG-negative prostate, gallbladder, and gastric cancers compared to corresponding control tissues ( Pollard et al, 2009 ; Silva et al, 2013 ; Wang et al, 2014 ; Zali et al, 2019 ; Muralidharan et al, 2020 ), which is consistent with our pancancer analysis of TCGA data showing higher GGH expression in numerous cancers including other gynecologic cancers. This elevated expression was observed at both protein and mRNA levels in UCEC patients.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported higher GGH expression levels in urothelial, invasive breast, ERG-negative prostate, gallbladder, and gastric cancers compared to corresponding control tissues ( Pollard et al, 2009 ; Silva et al, 2013 ; Wang et al, 2014 ; Zali et al, 2019 ; Muralidharan et al, 2020 ), which is consistent with our pancancer analysis of TCGA data showing higher GGH expression in numerous cancers including other gynecologic cancers. This elevated expression was observed at both protein and mRNA levels in UCEC patients.…”
Section: Discussionsupporting
confidence: 92%
“…During past decades, a panel of SNPs have been demonstrated to be associated with the susceptibility of cervical cancer. As demonstrated, these SNPs might serve as potential markers for risk evaluation, early diagnosis, sensitivity to clinical treatments, and prognosis prediction . In the present study, we reported that TT genotype of rs920778 strongly indicated a much higher risk of cervical cancer in Chinese women.…”
Section: Discussionsupporting
confidence: 56%
“…High GGH expression was shown to be associated with a higher risk of developing advanced toxicity to pemetrexed, a multi-targeted antifolate, in patients with advanced breast cancer (Llombart-Cussac et al 2007). Furthermore, several recently identified and characterized functionally significant genetic and epigenetic polymorphisms of GGH have been reported to predict response to and toxicity of antifolate-based treatment in patients with several cancers (Cheng et al 2004;Kim et al 2008;Koomdee et al 2012;Silva et al 2013;Smit et al 2012;Wang et al 2014) and inflammatory arthritis (Dervieux et al 2004;Hayashi et al 2009;Jekic et al 2013;Owen et al 2012;van der Straaten et al 2007;Yanagimachi et al 2011). Our data herein provide evidence that GGH modulation significantly influences expression and CpG DNA methylation of genes involved in important biological pathways that might account for the observed effects of GGH modulation on cancer risk, prognosis, and treatment response.…”
Section: Discussionsupporting
confidence: 54%